Statistical shape modeling of shape variability of the human distal tibia: implication for implant design of the tibial component for total ankle replacement - Yu, Jian; Li, Chengke; Lyu, Jinyang; Cao, Shengxuan; Zhang, Chao; Ma, Xin; Zhao, Dahang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionUnderstanding the morphological variability of the distal tibia can help design tibial components of total ankle implants. This study aimed to assess the shape variability of the distal tibial bone, utilizing the statistical shape modeling (SSM) technique.MethodsA total of 229 tibial bones were analyzed through CT scans to develop SSM models. Principal component analysis (PCA) was employed to characterize shape variation across the male, female, and overall groups. The geometric parameters of the resected surfaces at the 10-mm level above the distal tibial articular surface were compared.ResultsThe first seven principal component analysis (PCA) modes accounted for approximately 24.9%–40% of the shape variation, totaling 71.5%–75.6%. Considerable variabilities were observed among these three groups and all principal modes of variation. Notably, the male tibia had a bigger medial malleolus, anterior part of the fibular notch, and posterior malleolus. In the 10-mm resection surface of the distal tibia, anterior–posterior and medial–lateral distances were the main sources of variation. In addition, variations were frequently detected at both the anterior and posterior corners of the fibular notch in the resection surface of the distal tibia.ConclusionThe SSM technique has been shown to be an effective method in finding mean shape and principal variability. Size plays a crucial role in both inter- and intra-groups, and morphological differences vary across different sizes. Therefore, these considerations should be taken into account while designing tibial components for total ankle implants.